Analisis Kinerja Keuangan LSP ABC Jakarta dalam Penentuan Strategi Bisnis dengan Pendekatan Analisis SWOT - Renny Reswati; Haris Adi Swanoro; Rini Prasetyani; Dadan Hadiat Ramdany (Departement of Mathematics Education, 2023)
LSP ABC is an oil and gas certification service company located in the Duren Tiga, Pancoran, South Jakarta. At the beginning of 2020, economic, social and cultural activities began to be disrupted by the Covid-19 pandemic. This has an impact on the company, so that the certification application data in 2020 tends to decrease compared to the previous year, 2019. Therefore, it is necessary to analyze the company's financial ratios to find out the impact of this pandemic on the company's financial performance. This study aims to determine the company's financial condition using the ratio analysis method and managing business strategies using the SWOT analysis method to determine alternative strategies in determining decisions for the company so that company goals can be achieved. Data collection is done by interview the LSP ABC which is then processed and analyzed, the results obtained in the form of an average liquidity value of 2.874% which was above the company standard of 150%, the average solvency value of 92.6% according to the standard which is under 200%, and a profit of 24%. Based on these results, it can be concluded that the company's profits in 2020 decreased when compared to 2019 but the financial condition was in a good condition. Meanwhile, for business strategy analysis using SWOT, LSP ABC is in quadrant II position so it must diversify its business.